Cellular basis of learning and memory in the carotid body - Gold, Olivia M. S.; Bardsley, Emma N.; Ponnampalam, Anna P.; Pauza, Audrys G.; Paton, Julian F. R. (Frontiers in Synaptic Neuroscience, 2022)
The carotid body is the primary peripheral chemoreceptor in the body, and critical for respiration and cardiovascular adjustments during hypoxia. Yet considerable evidence now implicates the carotid body as a multimodal sensor, mediating the chemoreflexes of a wide range of physiological responses, including pH, temperature, and acidosis as well as hormonal, glucose and immune regulation. How does the carotid body detect and initiate appropriate physiological responses for these diverse stimuli? The answer to this may lie in the structure of the carotid body itself. We suggest that at an organ-level the carotid body is comparable to a miniature brain with compartmentalized discrete regions of clustered glomus cells defined by their neurotransmitter expression and receptor profiles, and with connectivity to defined reflex arcs that play a key role in initiating distinct physiological responses, similar in many ways to a switchboard that connects specific inputs to selective outputs. Similarly, within the central nervous system, specific physiological outcomes are co-ordinated, through signaling via distinct neuronal connectivity. As with the brain, we propose that highly organized cellular connectivity is critical for mediating co-ordinated outputs from the carotid body to a given stimulus. Moreover, it appears that the rudimentary components for synaptic plasticity, and learning and memory are conserved in the carotid body including the presence of glutamate and GABAergic systems, where evidence pinpoints that pathophysiology of common diseases of the carotid body may be linked to deviations in these processes. Several decades of research have contributed to our understanding of the central nervous system in health and disease, and we discuss that understanding the key processes involved in neuronal dysfunction and synaptic activity may be translated to the carotid body, offering new insights and avenues for therapeutic innovation.